Deepening Democracy for Viksit Bharat 2047: The Case of Bihar’s Special Intensive Revision and the Future of Electoral Inclusion - Sudarshanagouda M. Patil; Ashokkumar V. Paled, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
As India approaches the centenary of its independence in 2047, the realization of a Viksit Bharat is contingent upon the deepening of democratic processes through comprehensive electoral reforms. This paper examines the pivotal role of electoral inclusion in strengthening democracy, with a specific focus on Bihar’s Special Intensive Revision (SIR) exercise as a representative case study. Bihar’s diverse demographic and socio-political complexities provide a critical context for assessing efforts aimed at enhancing the accuracy and inclusivity of electoral rolls. The SIR initiative sought to systematically update voter lists, addressing issues of exclusion and inaccuracies to ensure universal suffrage. Through a detailed analysis of the implementation, achievements, and challenges of the SIR, this study elucidates the significance of meticulous electoral management in fostering greater voter participation and safeguarding electoral integrity. Looking forward, the paper underscores the necessity of sustained reforms—including the integration of technology and expanded voter education—to promote inclusive and transparent electoral practices across India. Bihar’s experience offers valuable insights into the future trajectory of electoral reforms necessary for consolidating democracy and achieving the vision of Viksit Bharat by 2047
Keywords: Electoral reforms; Voter inclusion; Special Intensive Revision; Bihar; Democratic deepening